Physical and chemical properties of the regional mixed layer of Mexico's Megapolis - P. Arnott; B. Rappenglueck; L. M. Russell; C. Ochoa; J. Allan; M. Grutter; D. Baumgardner (Atmospheric Chemistry and Physics, 2009)
The concentration of gases and aerosol particles have been measured at the mountain site of Altzomoni, 4010 m in altitude, located 60 km southeast of Mexico City, 50 km east of Puebla and 70 km northeast of Cuernavaca. The objective of this study was to evaluate the properties of gases and particles in the Regional Mixed Layer (RML) of Mexico's Megapolis. Altzomoni is generally above the RML from late evening until late morning at which time the arrival of the RML is marked by increasing concentrations of CO and aerosol particles that reach their maxima in mid-afternoon. The average diurnal cycles for fourteen days in March, 2006 were evaluated during which time the synoptic scale circulation had three principal patterns: from the east (E), southwest (SW) and west northwest (WNW). The original hypothesis was that air arriving from the direction of Mexico City would have much higher concentrations of anthropogenic gases and particles than air from Puebla or Cuernavaca, due to the relatively large differences in populations. In fact, not only were the average, maximum concentrations of CO and O3 (0.3 and 0.1 ppmv) approximately the same for air originating from the WNW and E, but the average maximum concentrations of Peroxyacyl nitrates (PAN,PPN) and particle organic matter (POM) in air from the E exceeded those in air from the WNW. Comparisons of measurements from the mountain site with those made by aircraft during the same period, using the same type of aerosol mass spectrometer, show that the total masses of POM, NO3−, SO42− and NH4+ were approximately the same from aircraft measurements made over Mexico City and when winds were from the east at the mountain site. In contrast 75% of the total aerosol mass at the mountain site was POM whereas over Mexico City the fraction of POM was less than 60%. The measurements suggest the occasional influence of emissions from the nearby volcano, Popocatepetl, as well as possible incursions of biomass combustion; however, the large concentrations of O3, PAN and POM suggest that secondary processes are the major source for these gases and particles. The similar concentrations in gases and particles when air is coming from the E and NWN raises the possibility of recirculation of air from Mexico City and the importance of this mechanism for impacting the regional air quality.